Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/membranes12020175
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Pyrolysis Temperature and TiO2-Incorporation on the Properties of SiOC/SiC Composites for Efficient Wastewater Treatment Applications

Abstract: This study focuses on the development of porous ceramer and SiOC composites which are suitable for microfiltration applications, using a mixture of polysiloxanes as the preceramic precursor. The properties of the membranes—such as their pore size, hydrophilicity, specific surface area, and mechanical resistance—were tailored in a one-step process, according to the choice of pyrolysis temperatures (600–1000 °C) and the incorporation of micro- (SiC) and nanofillers (TiO2). Lower pyrolysis temperatures (<700 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…However, it has been observed that the surface area of AAMs improves upon successive exposure to water and ion-exchange or by using a higher radius alkali cation in the synthesis (i.e., for example K silicate instead of Na silicate): in those cases, specific surface area can reach values of 100-300 m 2 g -1 (Melar et al, 2015;Skorina, 2014). The specific surface areas of the selective layers of conventional ceramic membranes can be > 600 m 2 g -1 (Ji et al, 2022) but they tend to decrease upon increasing the sintering temperature (e.g., a SiOC/SiC membrane had specific surface area of tens of m 2 /g when sintered at 800-1000 °C) (Fontão et al, 2022). The cumulative pore volume (Fig.…”
Section: Characterization Of the Membrane Materialsmentioning
confidence: 99%
“…However, it has been observed that the surface area of AAMs improves upon successive exposure to water and ion-exchange or by using a higher radius alkali cation in the synthesis (i.e., for example K silicate instead of Na silicate): in those cases, specific surface area can reach values of 100-300 m 2 g -1 (Melar et al, 2015;Skorina, 2014). The specific surface areas of the selective layers of conventional ceramic membranes can be > 600 m 2 g -1 (Ji et al, 2022) but they tend to decrease upon increasing the sintering temperature (e.g., a SiOC/SiC membrane had specific surface area of tens of m 2 /g when sintered at 800-1000 °C) (Fontão et al, 2022). The cumulative pore volume (Fig.…”
Section: Characterization Of the Membrane Materialsmentioning
confidence: 99%
“…Porous ceramics provide the opportunity to combine high porosity with crucial properties such as high thermal conductivity, high strength, and chemical stability, which are essential for industrial applications and development. The implementation of the materials includes catalytic support [1][2], removal of heavy metal ions or azo dyes from wastewater [3][4], thermal insulators [5], combustion analyzers [6], and membrane for microfiltration [7]. However, due to pricey raw materials and production techniques, the usage of porous ceramics in more widespread applications is restricted [8].…”
Section: ■ Introductionmentioning
confidence: 99%